2018
DOI: 10.12659/msm.910265
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Dehydrogenase 1 Silencing Expedites the Apoptosis of Non-Small Cell Lung Cancer Cells via Modulating DNA Methylation

Abstract: BackgroundNon-small cell lung cancer (NSCLC) accounts for about 85% of all types of lung cancer. Methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) is involved in DNA methylation, and DNA methylation is related to tumorigenesis. The role of MTHFD1 in NSCLC was examined in our study.Material/MethodsThe correlation between the expression of MTHFD1 and the clinicopathological features of patients diagnosed with lung cancer was investigated using the chi-square test. The viability and apoptosis of NCI-H1299 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…Lung cancer is one of the most common and aggressive tumors worldwide, with extremely high morbidity and mortality rates [1]. Among diagnosed lung cancer cases, approximately 80–85% are non-small cell lung cancer (NSCLC) [24]. Although advances in diagnosis and treatment have been made in NSCLC, the 5-year survival rate and recurrence rate remain poor [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common and aggressive tumors worldwide, with extremely high morbidity and mortality rates [1]. Among diagnosed lung cancer cases, approximately 80–85% are non-small cell lung cancer (NSCLC) [24]. Although advances in diagnosis and treatment have been made in NSCLC, the 5-year survival rate and recurrence rate remain poor [5].…”
Section: Introductionmentioning
confidence: 99%
“…It usually catalyzes sequential and reversible reactions in multiple conversion of tetrahydrofolate (THF), the active form of folate, into 5,10 methylene-THF, which is essential for the de novo purine and thymidylate synthesis as well as the supply of one-carbon units for subsequent DNA methylation. The de ciency or dysregulation of the MTHFD1 enzyme may in uence cell division and global methylation pattern, eventually contributing to tumorigenesis (Ding, et al 2018, MacFarlane, et al 2011). Since rs8003567 located in the intronic region of the MTHFD1 gene and no disease-related studies on SNPs have been reported before, another possible explanation cannot be excluded that there are additional functional genetic variants in linkage disequilibrium with these two SNPs that modify BC risk in Chinese female population.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic regulation of metabolism-related genes has also been reported in several studies that have attracted our attention. MTHFD1L silencing reduced proliferation and enhanced the apoptosis of non-small cell lung cancer by suppressing DNA methylation (40). MTHFD1L supports the Flow of Mitochondrial One-carbon Units into the Methyl Cycle in Embryos as well (22).…”
Section: Discussionmentioning
confidence: 99%